The nature of Jade - Caletti, Deb. (New York : Simon & Schuster Books for Young Readers, 2007)
Seattle high school senior Jade's life is defined by her anxiety disorder and dysfunctional family, until she spies a mysterious boy with a baby who seems to share her fascination with the elephants at a nearby zoo.
Keywords: Coming of age -- Juvenile fiction; Elephants -- Juvenile fiction; Zoos -- Juvenile fiction; Families -- Juvenile fiction; Anxiety -- Juvenile fiction; Seattle (Wash.) -- Juvenile fiction